2014
DOI: 10.1088/1741-2560/12/1/016009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spike sorting and thresholding of voltage waveforms for intracortical brain–machine interface performance

Abstract: Objective For intracortical brain-machine interfaces (BMIs), action potential voltage waveforms are often sorted to separate out individual neurons. If these neurons contain independent tuning information, this process could increase BMI performance. However, the sorting of action potentials (“spikes”) requires high sampling rates and is computationally expensive. To explicitly define the difference between spike sorting and alternative methods, we quantified BMI decoder performance when using threshold-crossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 43 publications
6
74
2
Order By: Relevance
“…We confirm previous findings that the hash should not be discarded, as it substantially increases decoding accuracy when included along with sorted spike counts (Todorova et al, 2014; Christie et al, 2015; Oby et al, 2016). Since sorted spike counts traditionally do not include hash, while threshold crossing counts do include hash, a comparison between these two methods is actually comparing two factors: presence of hash and use of spike sorting.…”
Section: Introductionsupporting
confidence: 90%
“…We confirm previous findings that the hash should not be discarded, as it substantially increases decoding accuracy when included along with sorted spike counts (Todorova et al, 2014; Christie et al, 2015; Oby et al, 2016). Since sorted spike counts traditionally do not include hash, while threshold crossing counts do include hash, a comparison between these two methods is actually comparing two factors: presence of hash and use of spike sorting.…”
Section: Introductionsupporting
confidence: 90%
“…This is not surprising given that in offline analyses multiunit activity and threshold crossings have yielded decoding performance and encoding fidelity that is comparable to or better than sorted spikes or local field potentials (Stark and Abeles 2007, Ventura 2008, Chestek et al 2011, Kloosterman et al 2014, Malik et al 2014, Todorova et al 2014, Christie et al 2015, Perel et al 2015). Recently, we and others have begun to recognize the need to investigate threshold setting in a principled way.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we and others have begun to recognize the need to investigate threshold setting in a principled way. Christie and colleagues (Christie et al 2015) found optimal thresholds for decoding performance to be between 3–4.5 times the rms voltage ( V rms ). Importantly, they only considered threshold settings from 3–18 × V rms ; they did not consider threshold crossings at lower threshold settings.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the current study (T6 and T7) used simpler threshold crossing counts as neural features. These features demonstrated nearly equivalent decoding performance and the potential for greater stability in NHP studies 21,22 and were used in a previous clinical study 1 .…”
mentioning
confidence: 99%